Effects of an external load on anticipatory mechanisms of handstand walking initiation in experienced gymnasts - Grabowiecki, M., Rum, L.; Laudani, L.; Vannozzi, G. (Journal of Sports Sciences, 2025)
Anticipatory postural adjustments (APAs) are responsible for a successful first step execution in handstand walking. This study evaluates gymnasts` ability to adapt their APAs and stepping parameters in response to adding/removing an external load over repeated handstand walking initiation trials. Eighteen gymnasts performed five handstand walking initiation trials without load (PRE), eight trials with an external load (LOAD) and five trials with removed load (POST). Force platforms and a motion capture system were used to quantify mechanical parameters from the anticipatory phase and the stepping phase. During the first LOAD trial, APAs did not change, however, the step height decreased by 0.56 cm compared to PRE (p = 0.007). During the second and third LOAD trials, the mediolateral center of pressure APAs increased by 2.0 cm (p = 0.01) and 2.3 cm (p = 0.01) compared to the first LOAD trial, while the step parameters returned to baseline. The removed load did not change APAs, while the step parameters were initially altered and then returned to baseline. Results show gymnasts` ability to modify their APAs over repeated trials to adapt to an external load, enabling them to initiate accurate forward steps. Training exercises should target handstand walking preparatory mechanisms for a smooth transition between handstand and stepping.